Binding ability and assembly behavior of β-cyclodextrin complexes with 2,2'-dipyridine and 4,4'-dipyridine - Liu, Yu (2011)
Two channel-type supramolecular aggregations 1 and 2 were prepared by the inclusion complex of â-cyclodextrin with 2,2′-dipyridine and 4,4′-dipyridine, respectively, and their binding ability and